Ovarian Mucinous Cystadenoma with Anaplastic Carcinoma Arising in The Mural Nodule: A Case Report - Bodepudi, Srija; M, Susruthan; G, Barathi (Annals of Pathology and Laboratory Medicine, 2018)
Mural nodules in cystic ovarian neoplasms are very rare. Mural nodules are localized thickened nodular areas occurring in the wall of cystic mucinous or serous tumors of the ovary. Histologically they may be benign reactive sarcoma like lesions or malignant lesions like sarcomas and anaplastic carcinomas. We report a case of mural nodule of anaplastic carcinoma in a mucinous cystadenoma of ovary.